Mario Arroyo Martínez Fabre, Ciencia y Fe ¿Un equilibrio posible? Lima, Fondo Editorial UCSS, 2015 - Eguiguren, Luis (Mercurio Peruano, 2020)
Mario Arroyo Martínez Fabre, Ciencia y Fe ¿Un equilibrio posible? Lima, Fondo Editorial UCSS, 2015